“La acción rescisoria y resolutoria en el derecho comparado Latinoamericano” - Jéssica Margarita, Pérez Pérez (2020)
This research project "Rescission and resolution action in Latin American Comparative Law"; ways to extinguish the obligations that arise from the real contest of wills of two or more parties. Termination, applicable due to the ineffectiveness existing at the time of its conclusion. It operates due to the non-observance of substantial requirements that must be observed for each type of contract. The second Resolution operates in the face of unsuccessful inefficiency, that is, in the face of events that occur after the conclusion of the contract validly performed. The importance of this study is framed in the area of Civil Law, insofar as contracts and obligations have to do. Specifically, in this topic, we talk about ways to extinguish obligations, given the real contest of wills the parties make their assets and interests available. The scope of this legal study of rescission action and resolution action in Latin American Comparative Law is to achieve: students, teachers, legal professionals, and other interested parties, an understanding of these legal figures, understanding their real legal sense, with them in order to use them correctly. The unit of analysis was located in the legal system of Latin American countries such as Chile, Mexico, Argentina, and Ecuador, studying in a particular way to be able to reach general conclusions in Comparative Law. The need to carry out this analysis has been seen due to the basic knowledge that we have of them and that we often use it in the wrong way due to the confusion that exists in this regard.